Sustainability Status Analysis of Berau’s Agriculture Sector: A Multi-Aspect Sustainability Approach (MSA) - Aprylasari, Dede; Toyibulah, Yoga; Nugroho, Agung Enggal; Azizah, Siti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study evaluates the sustainability status of the agricultural sector in Berau Regency, East Kalimantan, using a Multiaspect Sustainability Analysis (MSA) approach supported by EXSIMPRO software. The assessment focuses on three main dimensions: economic, institutional, and technological sustainability. Primary data were obtained from 30 key stakeholders, including farmers, extension officers, cooperatives, and local government representatives, and were complemented by secondary data from official sources. The results show that the economic sustainability index is 42.86%, indicating a low level of sustainability, mainly due to low productivity, fluctuating Farmer Exchange Rates (NTP), and limited market access. The institutional dimension records a borderline sustainability status of approximately 50%, reflecting weak farmer organizations, limited extension intensity, and insufficient regulatory support. The technological dimension performs relatively better, with a sustainability index of 65.8%, driven by partial adoption of agricultural machinery, superior seeds, and basic digital technologies. Leverage sensitivity analysis reveals an equal leverage value of 0.5 across all dimensions, indicating strong interdependence and the need for simultaneous, integrated interventions. Scenario simulations suggest that targeted policies could increase the economic sustainability index to 50% and the technological index to 87.5%. Key structural constraints include long marketing chains, inadequate irrigation, land conversion, labor shortages, and low digital literacy. The study concludes that integrated interventions focusing on technology adoption, institutional strengthening, and market access improvement are essential to enhance the overall sustainability of Berau Regency’s agricultural sector.